DESCRIPTION THE DURATION USAGE OF GADGETS ENERGY CONSUMPTION LEVEL AND OBESITY STATUS IN STUDENTS OF JUNIOR HIGH SCHOOL 10 DENPASAR - Cahyaning Werdiasih Pande; Ni Komang Wiardani; Lely Cintari (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2021)
Unhealthy diet, low physical activity like less work-out, not a lot of movement outside the room and play gadgets such as mobile phones. The negative impact of the use of gadgets, namely sleep disorders, brain growth that is too rapid, hindering child development, child obesity and mental disorders in children. The purpose of this research is to know the description of the status of obesity based on duration of usage of gadgets and levels of consumption of energy in students of Junior High School 10 of Denpasar. The type of research used namely observational and Purposive Sampling method using. Data collected that is the identity of the sample, the measurement data of Anthropometry, duration of usage of gadgets and the level of energy consumption samples. The number of samples that are used as much as 91 samples. Based on the results of the study, groups of samples with the nutritional status of obesity that has duration of usage of gadgets with a duration of 2 hours per day that is as much as 20 samples (41.7%) and duration of over 2 hours as many as 48 samples (58.3%). As for the energy consumption level of the sample with the status of obesity has a rate of consumption above the adequacy as much as 39 samples (81.3%). This indicates that the duration of the use of gadgets more than 2 hours per day above consumption levels and adequacy ( 110% AKE) relating to the status of obesity in students of Junior High School 10 of Denpasar. Keywords: Obesity, Duration Usage Of Gadgets, The Level Of Energy Consumption